PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP NILAI PERUSAHAAN DENGAN VARIABEL INTERVENING PROFITABILITAS - Achmad Tjahjono; Siti Chaeriyah (Kajian Bisnis Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2017)
The Company was founded with the goal of increasing the value of the company as well as to provide prosperity for the owners or shareholders. Good Corporate Governance and profitability is an effort to enhance company value. This study aims to determine the influence of good corporate governance to company value with profitability as intervening variable. The population of this research is manufacturing companies listed in Indonesia Stock Exchange in 2010 - 2014. The sample is taken by using purposive sampling method. Under this method, as many as 123 companies were obtained. The analysis tool to test the hypothesis is path analysis with AMOS software version 21. Data analysis method is descriptive analysis, path analysis, and sobeltest. The results of this study indicate that managerial ownership, the audit committee and the profitability have positive impact toward the of the company value, institutional ownership has positive impact but not significant, non-executive director with negative effect tendency on the company value. The results of this study also showed that profitability cannot mediate the effect of good corporate governance mechanisms on company value. It can be suggested to replace the intervening variable with other variables such as quality of earnings instead of profitability since it is declined as an intervening variable. non-executive director and institutional ownership does not contribute any positive and significant effect on company value and profitability. The following research can use another proxy in the measurement process and consider other theories that could explain comprehensively.